ANALISIS KEBIJAKAN DINAS PENDIDIKAN KOTA PEKALONGAN DALAM MENEGAKKAN ETIKA PROFESI GURU DI ERA DIGITAL: STUDI IMPLEMENTASI KEBIJAKAN 2020–2026 - Ziyadah El Fadlillah; Rahma Nafalina Azzahra; Amelia Gita Maharani; Nur Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the policy of the Pekalongan City Education Office in enforcing teacher professional ethics in the digital era during the 2020–2026 period. The problem addressed is the increasing number of ethical violations by teachers in digital spaces, influenced by rapid technological development and uneven digital literacy. The objective of this research is to analyze policy implementation, identify challenges, and formulate recommendations to improve its effectiveness. This study employs a qualitative approach using literature review, policy analysis, documentation, and interviews with relevant stakeholders. The data are analyzed using content analysis to obtain a comprehensive understanding of the phenomenon. The findings indicate that the policy has a strong foundation, emphasizing professionalism, integrity, and responsible use of digital media, supported by training programs, supervision, and socialization. However, its implementation faces several challenges, including unequal understanding among teachers, inconsistent application across schools, limited digital literacy, and the rapid evolution of technology. Therefore, strengthening continuous training, providing clear technical guidelines, improving supervision systems, and enforcing consistent sanctions are necessary to enhance policy effectiveness. This study contributes to the development of adaptive and responsive educational policies in maintaining teacher professionalism in the digital era.